THE IMPLEMENTATION OF TEAM GAME TOURNAMENT TECHNIQUE TO TEACH GAME TOURNAMENT OF HORTATORY EXPOSITION TEXT - Eka Yuliawati, - (2014)
This research was conducted to find out the effectiveness of team game tournament (TGT) technique to improve students' reading comprehension skill and to investigate the students' responses to the implementation of the technique. This research was carried out in a senior high school in Subang, involving 60 students who were divided into experimental and control groups. The quasi-experimental design was employed in this research. The data were collected through pre-test and post-test, questionnaire and interview with the students. The result showed that TGT technique was effective to improve students' reading comprehension skill, as seen from the significant difference in score between the experimental and control group. In addition, the students showed positive responses to the implementation of the technique as they claimed that they understood the learning material easier. They were also motivated to learn and they had a better relationship with their friends. On the other hand, some students claimed to be disturbed by the noise created during the activities. They were also bored to be in the same team for weeks.